Fine Pore‐Structure Engineering by Ligand Conformational Control of Naphthalene Diimide‐Based Semiconducting Porous Coordination Polymers for Efficient Chemiresistive Gas Sensing - Xue, Ziqian; Zheng, Jia‐Jia; Nishiyama, Yusuke; Yao, Ming‐Shui; Aoyama, Yoshitaka; Fan, Zeyu; Wang, Ping; Kajiwara, Takashi; Kubota, Yoshiki; Horike, Satoshi; Otake, Ken‐ichi; Kitagawa, Susumu (Angewandte Chemie International Edition, 2023)
Exploring new porous coordination polymers (PCPs) that have tunable structure and conductivity is attractive but remains challenging. Herein, fine pore structure engineering by ligand conformation control of naphthalene diimide (NDI)‐based semiconducting PCPs with π stacking‐dependent conductivity tunability is achieved. The π stacking distances and ligand conformation in these isoreticular PCPs were modulated by employing metal centers with different coordination geometries. As a result, three conjugated PCPs (Co−pyNDI, Ni−pyNDI, and Zn−pyNDI) with varying pore structure and conductivity were obtained. Their crystal structures were determined by three‐dimensional electron diffraction. The through‐space charge transfer and tunable pore structure in these PCPs result in modulated selectivity and sensitivity in gas sensing. Zn−pyNDI can serve as a room‐temperature operable chemiresistive sensor selective to acetone. Conjugated 3D naphthalene diimide (NDI) based conductive porous coordination polymers (PCPs) with tunable conductivity and pore structure are developed as chemiresistors for room‐temperature gas sensors. The Zn−pyNDI can serve as a room‐temperature operable chemiresistive sensor selective to acetone.